Untangling The Dynamics of Socially Responsible Investing in Nepal: The Role of Behavioral Intentions and Financial Performance - Raghubansha, Suyesh Dev; Thapa, Bharat Singh; Pathak, Durga Datt (Journal of Business and Management, 2024)
Background: The increasing importance of socially responsible investment (SRI) globally highlights the need to understand the factors driving SRI decisions of individual investors. While significant research on factors affecting SRI has been conducted internationally, the context of Nepal remains largely underexplored. Objectives: This study examines how the attitude towards SRI, subjective norms, and perceived behavioral control influence the intention to invest in SRI, which subsequently impacts SRI behavior, while also analyzing the mediating role of intention in the relationship between perceived behavioral control and SRI behavior. Methods: This study employed a cross-sectional survey through a comprehensive questionnaire administered among 410 active individual investors in Nepal. Partial Least Squares Structural Equation Modeling (PLS-SEM) path analysis was conducted. Results: The findings reveal a positive and significant impact of attitude towards SRI on investor’s intention to invest in SRI. Interestingly, subjective norms and perceived behavioral control did not significantly impact the intention to invest in SRI. Furthermore, intention to invest in SRI and perceived behavioral control have a positive and significant impact on socially responsible investment behavior. Intention to invest in SRI did not play a significant mediating role between perceived behavioral control and SRI behavior. The study demonstrates a positive and significant moderating effect of the financial performance of SRI on the relationship between the intention to invest in SRI and SRI behavior. Conclusion: The study concludes that attitude significantly influences the intention to invest in SRI, while both intention and perceived behavioral control positively impact SRI behavior. Financial performance moderates the relationship between intention and behavior, emphasizing the need to foster positive attitudes and address financial performance to promote socially responsible investment among individual investors. JEL Classification: D53, G11, M14, Q01, O16